Sports doping in the adolescent athlete: The hope, hype, and hyperbole - Greydanus, D. E.; Patel, D. R. (Pediatric Clinics of North America, 2002)
A well-balanced diet with appropriate training is the key to maximizing athletic performance. Nutritional counseling should be an essential part of anticipatory guidance, especially for certain teens, such as those who are vegetarians or those with low-calorie intakes. Other considerations for anticipatory guidance are listed in Box 8. Adequate hydration before, during, and after practice or a game is important to maintain hemodynamic balance, prevent heat disorders, and optimize performance. Cool water is adequate for short-duration activities, while carbohydrate-electrolyte fluids are more desirable for long-term activities, especially those lasting more than an hour. Such drinks are also more palatable and the athlete is more likely to consume them. Carbohydrates (meaning hydrates of carbon) are an important part of the athlete's diet; carbohydrates are rapidly broken down and their energy is quickly supplied to the body. The body stores only a small amount of carbohydrates in the form of glycogen in the liver, while muscle glycogen is an immediate source of energy. Thus, carbohydrate loading has been used to increase glycogen stores and aid the athlete involved in endurance events.